2014
DOI: 10.1007/s11573-014-0743-3
|View full text |Cite
|
Sign up to set email alerts
|

How celebrity endorsers enhance parent brand extendibility to low similarity brand extensions

Abstract: To exploit further growth opportunities, firms increasingly consider extending their brands not only within related categories but also into categories that do not fit well with the parent brand. Prior research has shown that brand extensions with a low similarity with the parent brand are risky and may result in high failure rates. This research investigates the extent to which celebrity endorsements for a parent brand enhances its brand extension potential and allows a brand to accommodate more diverse exten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 84 publications
(123 reference statements)
1
5
0
Order By: Relevance
“…Therefore, either a healthy brand's name is kept well dissociated from non-healthy brands from the same manufacturer (for example, Quaker versus Sabritas), or an intermediate level of similarity is sought and it is handled as a brand extension. This proposal is in agreement with studies reported in the literature (Erfgen et al, 2015) that suggest that the relationship between similarity or fit with the Are brand extensions of healthy products an adequate strategy when there is a high association between the brand and unhealthy products? parent brand and the evaluation received by the brand extension is U-shaped, in which moderate similarity (elimination or substitution of notso-healthy ingredients) may have better results than high similarity (complete modification of ingredients).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Therefore, either a healthy brand's name is kept well dissociated from non-healthy brands from the same manufacturer (for example, Quaker versus Sabritas), or an intermediate level of similarity is sought and it is handled as a brand extension. This proposal is in agreement with studies reported in the literature (Erfgen et al, 2015) that suggest that the relationship between similarity or fit with the Are brand extensions of healthy products an adequate strategy when there is a high association between the brand and unhealthy products? parent brand and the evaluation received by the brand extension is U-shaped, in which moderate similarity (elimination or substitution of notso-healthy ingredients) may have better results than high similarity (complete modification of ingredients).…”
Section: Discussionsupporting
confidence: 91%
“…The strength of the brand credibility was shown to be the most important variable when deciding on brand extensions that are perceived as very original, in comparison with other marketing variables such as distribution. In the specific case of the food industry, the literature review regarding the perceived fit between the parent brand and brand extensions carried out by Erfgen, Sattler, and Schnittka (2015) confirms the popularity of the strategy of "transfering" favorable perceptions of the parent brand to new categories of food products and beverages; around 93% of the new products in the food market were brand extensions. This review suggests that in order to reduce the risk of low similarity with the parent brand it is important to get support from celebrities to increase positive consumer evaluations of the brand extension.…”
Section: Theoretical Frameworkmentioning
confidence: 81%
See 1 more Smart Citation
“…Celebrity endorsers are influential in forming positive or negative consumer attitudes based on the resemblances between the consumers' perceived self-image and the image of the celebrity (Erfgen et al, 2014;Albert et al, 2017). Factors that drive this influence include truthfulness, acceptability and attractiveness (Lunardo et al, 2015).…”
Section: Consumers' Attitude Towards Celebrity and Purchase Intentionmentioning
confidence: 99%
“…The conflict effect in this study might be not the same as that of previous goods-to-goods brand extension. Considered that the increased uncertainty and risk would be possibly perceived by consumers under the conditions of dissimilar extension category (Erfgen, Sattler, & Schnittka, 2015; Smith & Andrews, 1995), and the stronger the perceived risk, the higher the conflict (Jin, Zhang, & Chen, 2017; Wang, Meng, Liu, Wang, & Ma, 2016). Therefore, we speculate that N2 amplitude was more negative for LF conditions than HF conditions.…”
mentioning
confidence: 99%